2012
DOI: 10.2478/v10096-012-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Ichnology of Upper Cretaceous deep-sea thick-bedded flysch sandstones: Lower Istebna Beds, Silesian Unit (Outer Carpathians, southern Poland)

Abstract: Abstract:The Ophiomorpha rudis ichnosubfacies of the Nereites ichnofacies was recognized in thick-and very thickbedded sandstones of the Lower Istebna Beds (Campanian-Maastrichtian), which were deposited mainly in deep-sea clastic ramps and aprons. It contains mainly Ophiomorpha rudis (produced by deeply burrowing decapod crustaceans) and rarely Zoophycos isp. and Chondrites isp. The impoverished Paleodictyon ichnosubfacies of the Nereites ichnofacies is present in the medium-and thin-bedded packages of flysch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The Istebna sandstones of the Lower Campanian-Maastrichtian belong to the Silesian nappe [30,31], as shown in Figure 1. They are a product of deep-sea silicoclastic sedimentation in the diverse and rapidly changing deposition environments of the channels and their outlet zones of the central cone and within the non-canalized silicoclastic apron [32][33][34].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The Istebna sandstones of the Lower Campanian-Maastrichtian belong to the Silesian nappe [30,31], as shown in Figure 1. They are a product of deep-sea silicoclastic sedimentation in the diverse and rapidly changing deposition environments of the channels and their outlet zones of the central cone and within the non-canalized silicoclastic apron [32][33][34].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Phycosiphon is interpreted a trace of a deposit-feeding, wormlike organism (Wetzel & Bromley, 1994). Phycosiphon occurs in continental-shelf slopes, submarine fans, turbidites, and flysch deposits (e.g., Uchman, 1998;Naruse & Nifuku, 2008;Rajchel & Uchman, 2012). Recent studies have found that Phycosiphon tracemakers are early colonizers of the upper portions of turbidite deposits when bottom waters are fully oxygenated (e.g., Wetzel & Uchman, 2001;Naruse & Nifuku, 2008).…”
Section: Ichnogenus Phycosiphon Fischer-ooster 1858mentioning
confidence: 99%
“…1 and 2). The lithological-sedimentological fea tures, ichnofacies char ac ter is tics and strati graphic po si tion of the de pos its have been stud ied by a num ber of authors (e.g., Hohenegger, 1861;Liebus and Uhlig, 1902;Burtanówna, 1936;Burtanówna et al, 1937;Książ kiewicz, 1962;Unrug, 1963Unrug, , 1968Eliáš, 1970;Peszat, 1976;Menčík et al, 1983;Menčík and Tyráček, 1985;Ślączka, 1986;Żytko et al, 1989;Poprawa et al, 2002Poprawa et al, , 2004Strzeboński, 2005;Grzebyk and Leszczyński, 2006;Picha et al, 2006;Ślączka et al, 2006, 2012Golonka and Waśkowska-Oliwa, 2007;Cieszkowski et al, 2009Fe lix et al, 2009;Uchman, 2009;Rajchel and Uchman, 2012).…”
Section: Introductionmentioning
confidence: 99%